Rare Hemorrhagic Complex Cyst Containing Necrotic Ovary and Part of Fallopian Tube: Case Report - kataneh kazemi; Mohsen Rakhsha; fateme poorkhayyat; mahboubeh ghorbani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Ovarian cysts are fluid-filled sacs that lie on the surface of or within the ovary. Ovarian cysts can also be hemorrhagic. Hemorrhagic ovarian cyst rupture can release blood and fluid into the pelvis, presenting several risks to the patient. Case Presentation: A 22-year-old female patient with a history of primary infertility for 2 years presented with a complaint of abdominal pain that started a year ago, and on ultrasound, a cystic mass with dimensions of 113 x 50 x 80 and an irregular wall. There was a papillary protrusion in the right adnexa, and the tumor markers were normal, so due to the severe abdominal pain and stable cyst, he was scheduled for surgery. Conclusion: In women of reproductive age who report a history of primary infertility and present with complaints of intermittent and periodic pain, one of the differential diagnoses may be suspicion of a hemorrhagic cyst.